2014
DOI: 10.5296/jse.v4i4.6326
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Teachers Training Programs in Islamabad Model Collages

Abstract: The present study explored the variables that contribute to the effectiveness of teachers training program in Pakistan for the education sector on the use of information and computer technology trainings. A sample of 111 lecturers from federal government colleges in Islamabad was taken and with the help of a research questionnaire their response was recorded. On its basis the study determined that computer knowledge and skills have been imparted in the trainees but their effectiveness could have been increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The faculty members considered the learning and professional development activities that they have attended to be impactful as they understand the application of learning experience to improve the skills and knowledge in performing the tasks of a classroom teacher. However, the study conducted by Wei and Raja (2014) on the effectiveness of teacher training program in Pakistan revealed that training programs were unsuccessful in the development of skills for experienced teachers. It was also revealed that most learned skills were not applied in the classroom and the same traditional practices were applied by the trained teachers.…”
Section: Introductionmentioning
confidence: 99%
“…The faculty members considered the learning and professional development activities that they have attended to be impactful as they understand the application of learning experience to improve the skills and knowledge in performing the tasks of a classroom teacher. However, the study conducted by Wei and Raja (2014) on the effectiveness of teacher training program in Pakistan revealed that training programs were unsuccessful in the development of skills for experienced teachers. It was also revealed that most learned skills were not applied in the classroom and the same traditional practices were applied by the trained teachers.…”
Section: Introductionmentioning
confidence: 99%